Efficacy and safety of the fully human anti-tumour necrosis factor α monoclonal antibody adalimumab (D2E7) in DMARD refractory patients with rheumatoid arthritis: a 12 week, phase II study. Issue 12 (21st November 2003) - van de Putte, L B A; Rau, R; Breedveld, F C; Kalden, J R; Malaise, M G; van Riel, P L C M; Schattenkirchner, M; Emery, P; Burmester, G R; Zeidler, H; Moutsopoulos, H M; Beck, K; et al.
Abstract : Objectives: To evaluate efficacy, dose response, safety, and tolerability of adalimumab (D2E7) in disease modifying antirheumatic drug (DMARD) refractory patients with longstanding, active rheumatoid arthritis (RA). Methods: During a 12 week, double blind, placebo controlled study, 284 patients were randomly allocated to receive weekly subcutaneous injections of adalimumab 20 mg (n = 72), 40 mg (n = 70), or 80 mg (n = 72) or placebo (n = 70) without concomitant DMARDs. Results: Adalimumab significantly improved the signs and symptoms of RA for all efficacy measures. ACR20 responses with adalimumab were significant at each assessment versus placebo (p⩽0.01). Additionally, ACR responses with adalimumab were achieved more rapidly than with placebo, with 82/115 (71%) of the ultimate ACR20 response rate to adalimumab treatment achieved at week 2. At week 12, for adalimumab 20, 40, and 80 mg, ACR20 response rates were 50.7%, 57.1%, and 54.2%, respectively, versus 10.0% for placebo (p⩽0.001 for all comparisons); ACR50 rates were 23.9%, 27.1%, and 19.4%, respectively, versus 1.4% for placebo (p⩽0.001 for all comparisons); and ACR70 rates were 11.3%, 10.0%, and 8.3%, respectively, versus 0.0% for placebo (p⩽0.05 for all comparisons). All adalimumab doses significantly improved all ACR core criteria at all assessments. The 40 mg and 80 mg doses provided similar benefit. Adalimumab at all doses was generally well tolerated, with only mild or moderate adverse events. Completion rates were 87% for adalimumab and 67% for placebo. Conclusions: Adalimumab given as monotreatment to patients with longstanding, severe RA refractory to traditional DMARDs produced a rapid, sustained response and was safe and well tolerated, with no dose limiting side effects.